Detection and genetic characterization of rotavirus infections in non-hospitalized children with acute gastroenteritis in Japan, 2007-2009 - Chan-It W. (2014)
The molecular epidemiology of rotavirus infections in non-hospitalized children in five different regions (Sapporo, Saga, Tokyo, Osaka, and Maizuru) of Japan during 2007-2009 was investigated. Overall, rotavirus was detected in 156 out of 1008 (15.5%) specimens. The rotavirus infection in 2007-2008 (19.3%) was higher than those in 2008-2009 (12.1%). G1P[8] was the most prevalent (62.8%), followed by G3P[8] (21.8%), G9P[8] (14.7%), and G2P[4] (0.7%). Interestingly, the number of G3P[8] strains increased threefold from the former season (2006-2007) from 7.3% to 21.8%, whereas G2P[4] and G9P[8] decreased from 11.4% to 0.7% and 20.3% to 14.7%, respectively. In the phylogenetic analysis, G3 rotaviruses were closely related to " the new variant G3" 5091 strain, which previously emerged in Japan and China. G9 viruses isolated in 2007-2008 were genetically close to the Thai strain, while those isolated in 2008-2009 had a close relationship with Chinese strains. G1 viruses appeared to be more similar to the recently reported G1 strain in China. Nucleotide sequence analysis of 33 P[8]-nontypeable strains revealed 5 nucleotide mismatches at the primer binding site. Based on previously reported (2003-2007) and current (2007-2009) data of rotavirus surveillance in the five areas of Japan, it was revealed that in Sapporo, Osaka, and Maizuru, G1P[8] and G3P[8] were detected at high frequencies, ranging from 47.2 to 57.7% and 31.7 to 47.4%, respectively. In Tokyo, G1P[8] (47.4%) was the predominant strain, followed by G9P[8] (20.6%), whereas in Saga, G3P[8] (38.9%) and G9P[8] (36.1%) were identified as the most dominant types. None of G9P[8] was detected in Sapporo. This study highlights the genetic diversity and the significance of rotavirus diarrhea in Japan. © 2010 Elsevier B.V.